Gambaran Kadar TSH, FT3 dan FT4 pada Pasien Gangguan Tiroid di RSUD Anutaloko Parigi - Khafifa Usnul Mar’iyah Dg Tompo; Nazula Rahma Shafriani; Farida Noor Irfani (Yayasan Literasi Sains Indonesia, 2025)
Thyroid disorders are a problematic condition in individuals due to dysfunction of the thyroid gland, such as changes in its form and function. The most common thyroid disorders include hyperthyroidism and hypothyroidism. This study aims to identify and analyze TSH, FT3, and FT4 levels in individuals diagnosed with thyroid disorders. This research uses a cross-sectional method by collecting secondary data. Secondary data for this research was obtained from records of TSH, FT3 and FT4 hormone examinations in the laboratory at Anutaloko Parigi Regional Hospital. This data covers the period January to December 2024, then processed and analyzed using descriptive statistical tests in SPSS, then presented in table format. Based on age characteristics, the majority of respondents with thyroid disorders were aged 25-59 years with a percentage of 25 people with hyperthyroidism and 11 people with hypothyroidism. Respondents with the most thyroid disorders were diagnosed with hyperthyroidism rather than hypothyroidism. The total number of patients who had TSH, FT3 and FT4 checked at Anutaloko Parigi Regional Hospital found that patients with hyperthyroidism were predominantly female and aged 25-59 years.